Research on the motion trajectory control of industrial manipulators by the incremental PID control optimization algorithm - Wang Jicai; Chen Fangyan (Mechanics & Industry)
With the wide application of industrial manipulators, the research of its moving trajectory control method has become more and more important content. In this paper, the motor closed-loop control strategy of an industrial 6R manipulator was briefly introduced, the proportional, integral, and differential ( (PID) algorithm commonly used in motor control was analyzed, and its shortcomings were pointed out. Then, the incremental PID algorithm was introduced to design a grey wolf optimization (IGWO) algorithm to achieve parameter tuning. Simulation experiments were carried out in a MATLAB environment. The results showed that the incremental PID algorithm generated a smaller control deviation than the PID algorithm. The average deviation of the three axes of the incremental PID algorithm undergoing IGWO parameter tuning was less than 0.2 mm, and the moving time was between 1.1 s and 1.3 s. The control accuracy and efficiency of the incremental PID algorithm undergoing IGWO parameter tuning were better than those of the incremental PID algorithm whose parameters were tuned using the trial-and-error method and the grey wolf optimization algorithm respectively. Moreover, better stability and anti-interference were observed in step response and sinusoidal response. The results prove that the incremental PID algorithm combined with the IGWO algorithm is reliable in the moving trajectory control of industrial manipulators and can be applied in practice.